School practice of media literacy – Document analysis - HERZOG, Csilla (Journal of Education, Technology and Computer Science, 2016)
Digital competens belongs to one of the key competens in the Hungarian education as well. This study examines the written documents which are related to media literacy with the help of the document analysis method. We have proved the fact, due to the written documents and the devel-opment plans, that with a well-planned and well-built media education we could cover several different cross-curriculum areas and ensure wide range of education goals.